Adverse effects of finerenone in patients with heart failure: a systematic review and meta-analysis - Yu, Wanqian; Luo, Fan; Rao, Jingan; Lei, Guangtao; Wu, Qinghua; Shen, Wen; Yang, Pingping; Li, Ping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFinerenone has been shown to improve outcomes in patients with heart failure (HF), encompassing those with reduced (HFrEF), mildly reduced (HFmrEF), or preserved ejection fraction (HFpEF). However, its clinical use is accompanied by notable adverse effects. This study aimed to evaluate the relative risks of adverse events associated with finerenone across HF phenotypes.MethodsA systematic search of PubMed, Embase, and Web of Science identified six randomized controlled trials involving 8,527 HF patients. The analysis considered hyperkalemia, hypotension, treatment-emergent adverse events (TEAEs), treatment-emergent serious adverse events (TESAEs), and treatment discontinuation due to adverse events.ResultsFinerenone significantly increased the risk of hyperkalemia (RR = 2.07, 95% CI 1.77-2.44, P < 0.00001) and hypotension (RR = 1.49, 95% CI 1.31-1.68, P < 0.00001) compared to placebo, irrespective of HF phenotype. No significant differences were observed between finerenone and placebo in terms of TEAEs, TESAEs, or treatment discontinuation when analyzing the overall heart failure population. Compared to eplerenone, finerenone was associated with a lower risk of TEAEs (RR = 0.93, 95% CI: 0.89-0.98) and TESAEs (RR = 0.74, 95% CI: 0.66-0.84), with similar discontinuation rates. Additionally, one included study suggested that finerenone may have a lower risk of TEAEs (RR = 0.64, 95% CI 0.56-0.74), treatment discontinuation (RR = 0.37, 95% CI 0.25-0.54) and hyperkalemia (RR = 0.41, 95% CI 0.21-0.79) compared to spironolactone, with similar rates of hypotension (RR = 0.61, 95% CI 0.29-1.30) in HFrEF.ConclusionFinerenone (10-25 mg) showed a similar safety profile to placebo, with no significant differences in TEAEs, TESAEs, or treatment discontinuation. Compared to eplerenone, finerenone was associated with fewer TEAEs and TESAEs, with comparable discontinuation rates. Moreover, in patients with HFrEF, finerenone may offer lower risks of TEAEs, treatment discontinuation, and hyperkalemia than spironolactone, with similar rates of hypotension.